Type beta transforming growth factor reversibly inhibits the early proliferative response to partial hepatectomy in the rat. - Russell, W E (1988)
Type beta transforming growth factor (TGF-beta), a factor produced by many cell types, is a potent inhibitor of hepatocyte DNA synthesis in vitro. To determine whether TGF-beta can influence hepatocyte proliferation in vivo, its effects were examined on the regenerative response of liver to partial hepatectomy (PH) in the rat. Porcine platelet-derived TGF-beta 1 (0.5 micrograms), administered intravenously at the time of PH and 11 hr later, reduced the fraction of hepatocytes engaged in DNA synthesis 22 hr after PH by 67% and inhibited the rate of hepatic [3H]thymidine incorporation by 50%. TGF-beta 2 produced a similar effect. A single dose of 0.5 micrograms of TGF-beta 1 given 11 hr after PH reduced liver [3H]thymidine incorporation by 32%; 4.5 micrograms of TGF-beta 1 or TGF-beta 2 inhibited DNA synthesis by 88% and the labeling index by 86%. Although sensitive to TGF-beta administered 11 hr after PH, late in the G1 phase of the cell cycle, a single dose of 0.5 micrograms given at the time of PH did not significantly influence DNA synthesis 22 hr after PH. The inhibitory effects of TGF-beta were transient; rats treated with two 0.5-microgram doses of TGF-beta at 0 and 11 hr had completely restored their original liver DNA mass 8 days after PH. Administration of 0.5 microgram of either TGF-beta 1 or TGF-beta 2 every 12 hr for 5 days failed to suppress the recovery of hepatic DNA mass. However, the nuclear labeling index of the TGF-beta-treated animals was significantly higher than that of the controls. There was no evidence of cytotoxicity from TGF-beta, as determined by liver histology and plasma concentrations of glucose, insulin-like growth factor I, and two hepatic enzymes. Thus, TGF-beta 1 and TGF-beta 2 reversibly inhibit the proliferative response of liver to PH and may be important in the modulation of normal liver growth and repair.